History and Status of Eucalyptus Improvement in Florida - Donald L. Rockwood (International Journal of Forestry Research)
The first organized Eucalyptus research in Florida was begun by the Florida Forests Foundation in 1959 in southern Florida. This research was absorbed by the USDA Forest Service and the Florida Division of Forestry in 1968. In the early 1970s, the Eucalyptus Research Cooperative formed to provide additional support emphasized E. grandis, E. robusta, E. camaldulensis, and E. tereticornis and developed cultural practices for commercial plantations in southern Florida. In 1978, this cooperative united with the Hardwood Research Cooperative at North Carolina State University until 1985 when the 14-year effort ended after three severe freezes from 1983 to 1985. Eucalyptus planting and research were continued with a Florida-wide focus by the University of Florida and collaborators starting in 1980. The collective accomplishments in terms of genetic resources and commercial planting are summarized. For example, fast-growing, freeze-resilient E. grandis seedlings are produced by advanced generation seed orchards, five E. grandis cultivars are commercially available, as are E. amplifolia and Corymbia torelliana seeds. Genetic improvement of these and other species is ongoing due to beneficial collaborations. Short Rotation Woody Crop systems are promising for increasing productivity and extending uses beyond conventional pulpwood to applications such as windbreaks, dendroremediation, and energy wood.